2018
DOI: 10.1002/dvdy.24635
|View full text |Cite
|
Sign up to set email alerts
|

Reduced embryonic blood flow impacts extracellular matrix deposition in the maturing aorta

Abstract: The DA's response to hemodynamic perturbations invokes coupled mechanisms for shear regulation and matrix maturation, potentially impacting the course of vascular development. Developmental Dynamics 247:914-923, 2018. © 2018 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 54 publications
0
10
2
Order By: Relevance
“…Despite its reputation as a regular of vascular remodeling (Brownlee & Lowell, 1991; Kamiya & Togawa, 1980; Langille & Donnell, 1986), WSS alone does not appear to be a strong driver of PAA wall remodeling and maturation at this stage in development. Our results are in contrast to the findings Espinosa et al (2018), who hypothesized that the decrease in WSS, due to decreased flow, prompted a series of adaptation mechanisms. We believe that perceived changes may have been a combination of the new strain added to the vascular wall, as seen with ventricular ligations (deAlmeida, McQuinn, & Sedmera, 2007), as well as changes in wall shear stress levels.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Despite its reputation as a regular of vascular remodeling (Brownlee & Lowell, 1991; Kamiya & Togawa, 1980; Langille & Donnell, 1986), WSS alone does not appear to be a strong driver of PAA wall remodeling and maturation at this stage in development. Our results are in contrast to the findings Espinosa et al (2018), who hypothesized that the decrease in WSS, due to decreased flow, prompted a series of adaptation mechanisms. We believe that perceived changes may have been a combination of the new strain added to the vascular wall, as seen with ventricular ligations (deAlmeida, McQuinn, & Sedmera, 2007), as well as changes in wall shear stress levels.…”
Section: Discussioncontrasting
confidence: 99%
“…While many of the tunica media studies have been qualitative, rather than quantitative, their studies are nevertheless consistent with current results, namely, the gradual increase in medial cell layers from HH24 onward, gradual increase in organization of the tunica media into continuous fibers (Bergwerff et al, 1996), the distinguishable “compact dense zone” that marks the vessel wall (Hughes, 1943), as well as the “marked increase” in vessel wall thickness between day 5 and 7. The relationship between these two factors, hemodynamic forces and cellular media composition was recently explored by Espinosa et al (2018). They found that increase in tunica-media content was more broadly affected by vitelline vein ligation than increase in wall organization.…”
Section: Discussionmentioning
confidence: 99%
“…The simultaneous measurement of dorsal aortic pressure and flow following VAL reveals an acute adaptive response to maintain pressure at the expense of blood flow [ 220 ] and chronic remodeling of the dorsal aorta resulting in increased stiffness, pulse-wave velocity, and vascular collagen content ( Figure 14 ) [ 221 ]. More recent studies have confirmed a role for altered arterial mechanical loading on arterial cellular composition [ 41 ] relevant to the aortopathy noted in patients with bicuspid aortic valves and enlarged aortas [ 42 ].…”
Section: Chronic Interventional Models Investigate the Relationshimentioning
confidence: 98%
“…The key findings of these studies included the progressive electrophysiologic maturation of the developing myocardium, the ability of the heart to generate phasic pressure and pulsatile blood flow in the absence of mature cardiac valves, including the contribution of the contracting conotruncus (CT) in the early embryo [ 21 ] and the impact of altered intracardiac blood flow on ventricular and vascular morphogenesis. Approaches explored in avian embryos [ 30 , 31 , 32 , 33 , 34 ] have broadened to mammalian embryos with advances in murine genetic models [ 35 , 36 , 37 ] and Drosophila [ 38 ], Xenopus [ 39 ], and zebrafish embryos [ 40 ] due to the ease of fate mapping and genetic tools, and have been applied to understand the opportunities for intervention and prevention in the human embryo and fetus [ 41 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there are several works in the literature investigating the disturbed hemodynamics following VVL and CTB (Espinosa et al 2018 ; Hogers et al 1997 ; Rugonyi et al 2008 ; Shi et al 2013 ), little has been reported for LAL. A comprehensive understanding of cardiac hemodynamics in the developing avian heart following LAL would enhance our current understanding of HLHS development.…”
Section: Introductionmentioning
confidence: 99%